Food pornography as applied to street food in Davao City - Rosos, Jofraine G.
This thesis production focused on using the concept of Food Pornography in presenting and promoting street foods in Davao City to its locals and guests. To achieve this, the researcher had to do some research on pornography, food pornography, ways on producing the pornographic aesthetic, photography and the strategies to interpret them, and street food. She has also come across the different campaign ads that have used the concept of food pornography and included the techniques in some of her photographs, 5 weeks for the production and another 4 weeks for the post production stage, and was able to produce 5 sets of photographs. In the fifth and final set, the researcher created a hypothetical campaign ad to be able to help in creating a clear concept of photographs. She was able to produce 8 photographs with Banana cue, Fish balls, Kwek kwek, and Chicken skin as her subjects using the concept of Food Pornography.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts